Mechanism of Sevoflurane Anesthesia under Hypothermic Cardiopulmonary Bypass on Postoperative Atrial Fibrillation Rhythm in Patients Undergoing Mitral Valve Replacement. (28th June 2022) - Che, Hao; Lv, Yufang; Yao, Fang; Zhao, Fang; Zhao, Liyun
Abstract : Objective . It was to investigate the mechanism of atrial fibrillation after mitral valve replacement under extracorporeal circulation in patients with rheumatic heart disease under sevoflurane anesthesia maintenance and to provide scientific and effective basis for clinical treatment. Methods . Forty patients with rheumatic heart disease who underwent mitral valve replacement were randomly rolled into group I (sinus rhythm of propofol anesthesia, n = 10 ), group II (atrial fibrillation rhythm of propofol anesthesia, n = 10 ), group III (sinus rhythm of sevoflurane anesthesia, n = 10 ), and group IV (atrial fibrillation rhythm of sevoflurane anesthesia, n = 10 ). Inflammatory factors, free tissue of right atrium, and incidence of postoperative atrial fibrillation were compared among all groups. Results . (i) The serum levels of NT-proBNP, CRP, sST-2, IL-6, TNF- α, and TGF- β 1 in group II were higher than those in group I, group III, and group IV, and the indexes in group III were higher than those in group IV (P < 0.05 ). (ii) The relative expression levels of PLB, CaMK II, Bax, and TP53 in the free tissue of right atrium in group II were higher than those in group I, III, and IV, and the index levels in group IV were higher than those in group III (P < 0.05 ). (iii) The incidence of postoperative atrial fibrillation in group III (0.00%) was significantly lower than that in group I (30%), group II (50%), and group IV (40.0%), and group II (50%) was the highest (P < 0.05 ). Conclusion . The maintenance of sevoflurane anesthesia can improve the inflammatory response and myocardial tissue autophagy in patients with sinus rhythm and atrial fibrillation rhythm and can reduce the incidence of postoperative atrial fibrillation in patients.